Vampires, Revenant Souls, and Objects of Healing: Religious Remedies in Seventeenth- and Eighteenth-Century Czech Lands - Malý, Tomáš; Enenklová, Monika (Historical Studies on Central Europe, 2023)
This study searches for the characteristic features of religious healing in three phenomena of the seventeenth and eighteenth centuries: veneration of miraculous images, apparitions from Purgatory, and vampire incidences. All the examples originate from the Czech lands, and all were in some way related to the Catholic renewal or strengthening the Catholic faith in this region. Individual cases have been analyzed with regard to the social relevance of religious remedies, their connection to social problems, and the interaction between the actors involved. The authors draw attention to the link between physical and mental healing and show the key role of local spiritual authorities, especially members of religious orders and parish priests, in spreading practices of spiritual healing. The study reveals that, however theologically sensitive they might have been, the practices analyzed were apparently encouraged by the clergy and the social elites in the local communities, therefore they can hardly be associated only with the so-called popular piety of the rural folk.